Determinação de antidepressivos tricíclicos em sangue total por cromatografia líquida com detector de arranjo de diodos empregando microextração líquido-líquido dispersiva - Berlato, Dener Gomes (2021)
Psychoactive drugs are the main agents involved in cases of intoxication according to the Toxicological Information Center of Rio Grande do Sul (CIT-RS) and the National Toxic-Pharmacological Information System (Sinitox). Within the classes of drugs involved, the class of tricyclic antidepressants (ADTs) stands out, generating severe effects in cases of intoxication, with cardiotoxic effects, which can be fatal. The extractive technique was based on dispersive liquid-liquid microextraction (DLLME) using hexane as low density extracting solvent and methanol as dispersing solvent. Whole blood was the biological matrix of choice for the determination of the tricyclic antidepressants amitriptyline, imipramine and doxepin and their respective biotransformation products nortriptyline and desipramine. The samples were analyzed by liquid chromatography with a diode array detector, in order to assist in cases of poisoning from the University Hospital of Santa Maria located at the Federal University of Santa Maria (HUSM-UFSM). The limit of quantification was 10 ng/ml for amitriptyline and doxepin, 20 ng/ml for nortriptyline and 30 ng/ml for imipramine and desipramine. The mobile phase was constituted by KH2PO4 buffer (pH 2.5) and methanol (60:40) with a flow rate of 1.2 ml/min. The wavelength for the analysis was doxepin, amitriptyline and nortiptyline at 239 nm, imipramine and desipramine at 249 nm and the internal standard medazepam 255 nm. The DLLME developed in whole blood for the determination of ADTs developed proved to be a simple, reliable, robust and reproducible method that can be used in toxicology laboratories.